Peran Multidimensional Lingkungan Sekolah terhadap Kondisi Emosional Siswa Sekolah Dasar: Studi Kasus Kualitatif - Putri Widya Wati; Oktaviani Oktaviani; Muhammad Zulkarnain; Anna Carolina; Mareta Silaturi; Ana Swita; Liza Murniviyanty; Arizona Arizona (Journal of Society Counseling, 2026)
This study aims to analyze the role of the school environment in shaping the emotional well-being of elementary school students. The study used a descriptive qualitative approach with a case study method, conducted with third-grade students at SD Negeri 85 Palembang. The study subjects consisted of one teacher and six students, selected purposively. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions using thematic analysis. The results showed that students' emotional well-being is significantly influenced by three main dimensions of the school environment: social, physical, and cultural. Specifically, empathetic and communicative teacher-student interactions have been shown to increase students' self-confidence and active participation in learning. Supportive peer relationships encourage students' comfort and courage in expressing their opinions, while negative interactions, such as light teasing, tend to decrease self-confidence and learning engagement. Physically, clean, well-organized classrooms with good lighting and ventilation improve concentration and emotional stability, while noise and uncomfortable temperatures trigger restless behavior. Furthermore, a school culture that instills the values of discipline, responsibility, and mutual respect contributes to positive student emotional regulation. These findings indicate that the school environment acts as a complex and dynamic system in contextually shaping students' emotional states.